2015
DOI: 10.1002/adv.21534
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Thermal Intelligent Core/Shell Nanofibers by the Solution Coaxial Electrospinning Process

Abstract: In this study, the authors present a promising structure of shape-stabilized phase change materials (PCMs) with remarkable thermal energy storage capacity as core/shell phase change nanofibers. In this regard, solutions of polyethylene glycol (PEG) (as an important category of PCMs) and cellulose acetate (CA) were used as core and shell solutions, respectively. Electrospinning with a coaxial spinneret was performed, and nanofibers with the mean diameter of 545 nm under the controlled condition were produced. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…c) is more responsive to the applied voltage variations. Moreover, it can be deduced from the figures that the effect of applied voltage on the nanofibers diameter is more significant than other parameters …”
Section: Resultsmentioning
confidence: 99%
“…c) is more responsive to the applied voltage variations. Moreover, it can be deduced from the figures that the effect of applied voltage on the nanofibers diameter is more significant than other parameters …”
Section: Resultsmentioning
confidence: 99%
“…The coaxial electrospinning setup consisted of a coaxial double spinneret, a grounded collecting plate, two syringe pumps, and a variable DC high-voltage power generator, as shown in Figure 1 . The coaxial double spinneret included two concentrically arranged capillaries [ 20 ]. A certain amount of the two polymer solutions were contained separately in two plastic syringes connected to the coaxial spinneret, and the flow rate in each capillary was adjusted in a double-way medical syringe pump [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…28 However, due to the functionality of electrospinning method, many studies focused on improving the shortcomings exist in a typical electrospinning process. 64,[66][67][68] For example, some reports showed that by simultaneously elesctrospinning fibers and electrospraying the cell suspension, the cells will have high viability. 67,68 There are some studies that drugs were encapsulated into the fibers, whereas in other reports, the combination of both fiber and liposomes were used to encapsulate the drugs and control its rate of release.…”
Section: Electrospinningmentioning
confidence: 99%